Hyperfunction semigroups - M. Kostic, S. Pilipovic, D. Velinov (Siberian Branch of the Russian Academy of Sciences, 2015)
We analyze Fourier hyperfunction and hyperfunction semigroups with non-densely defined generators and their connections with local convoluted C-semigroups. Structural theorems and spectral characterizations give necessary and sufficient conditions for the existence of these semigroups generated by a closed possibly not densely defined operator A.
Keywords: Fourier hyperfunction semigroups, hyperfunction semigroups, structural theorems